South Caucasus – 20 Years of Independence - (:unkn) unknown (Friedrich-Ebert-Stiftung, 2011)
Meanwhile, we are able to look back on twenty years of independence of the three South Caucasian states. However, there is no other region of the former Soviet Union in which the emergence of state sovereignty was connected with so much bloodshed as in South Caucasus. Thus, the happiness about the act of national selfdetermination is at the same time subdued by the failure to resolve the diverging interests peacefully.
Keywords: Caucasus, South -- History; Caucasus, South -- Politics and government